2016
DOI: 10.1007/s00521-016-2361-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of flower pollination algorithm in load frequency control of multi-area interconnected power system with nonlinearity

Abstract: This work presents an application of bio-inspired flower pollination algorithm (FPA) for tuning proportional-integral-derivative (PID) controller in load frequency control (LFC) of multi-area interconnected power system. The investigated power system comprises of three equal thermal power systems with appropriate PID controller. The controller gain [proportional gain (K p ), integral gain (K i ) and derivative gain (K d )] values are tuned by using the FPA algorithm with one percent step load perturbation in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(38 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…Frequency response model of three-area thermal power systems are proposed in [65,66]. The LFC for three-area hydro power systems is marked out in [59,[67][68][69]. Load frequency controllers are designed for a hydro-thermal power system divided into three-areas [50,70].…”
Section: Three-area Power Systemsmentioning
confidence: 99%
“…Frequency response model of three-area thermal power systems are proposed in [65,66]. The LFC for three-area hydro power systems is marked out in [59,[67][68][69]. Load frequency controllers are designed for a hydro-thermal power system divided into three-areas [50,70].…”
Section: Three-area Power Systemsmentioning
confidence: 99%
“…To get the optimal value, velocity and position of particles is updated in successive iterations using Equations (13) and (14). The process continues till the stopping conditions is meet.…”
Section: Hybrid Molgsamentioning
confidence: 99%
“…In [10], the authors have studied the PID controller gains tuned by Imperialist Competitive Algorithm (ICA). Various novel technique/control approaches such as Firefly Algorithm (FA) optimized PI controller [11,12], Flower Pollination Algorithm (FPA) tuned PID controller [13], Grey Wolf Optimization (GWO) tuned classical controller with PI and PID structure [14], Differential Evolution (DE) tuned 2-DOF PID [15], TLBO tuned 2-DOF PID [16], ICA-based fuzzy-PI [17], hybrid FA and Pattern Search (hFA-PS) optimized PI and PID [18], A hybrid gravitational search algorithm (GSA) and PS tuned PI/PIDF controller [19], hybrid Stochastic Fractal Search and Local Unimodal Sampling (hSFS-LUS) optimized multistage PDF plus (1 + PI) [20] have been recently suggested for various types of power systems for frequency control.…”
Section: Introductionmentioning
confidence: 99%
“…Natural pollinators are simulated by using levy flights. Studies have revealed the ingenuity of the FPA algorithm over other metaheuristics [2,7,24,40]. Motivated by this, this algorithm has been employed in the current study in training the NNs of the HNN model.…”
Section: Metaheuristic Supported Neural Networkmentioning
confidence: 99%